2020
DOI: 10.1111/jcmm.15172
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of glaucoma by prostaglandin agonists and beta‐blockers in combination directly reduces pro‐fibrotic gene expression in trabecular meshwork

Abstract: Glaucoma is a disorder that eventually leads to optic neuropathy resulting in a compromise of visual field perception in a patient. It is the second leading cause of blindness worldwide and if left untreated can cause an irreversible loss of vision. 1 Primary glaucoma is of two types-primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG) based on the morphology of irido-corneal angle. In both the situations, there is an increase in the intraocular pressure (IOP) and eventually there is da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(106 reference statements)
0
7
1
Order By: Relevance
“…Animal studies also demonstrated an increase in outflow facility with Netarsudil therapy. [31] However, the Netarsudil concentration in that trial was higher (0.04% vs. 0.02% in our investigation), and two drops rather than one were administered to each eye. In this study both bimatoprost and netarsudil showed significant decrease in IOP, however, bimatoprost was found to be more effective in decreasing IOP in all patients as compared to netarsudil especially more in higher base line group.…”
Section: Ss-oct For Rnfl Onh Gcccontrasting
confidence: 59%
“…Animal studies also demonstrated an increase in outflow facility with Netarsudil therapy. [31] However, the Netarsudil concentration in that trial was higher (0.04% vs. 0.02% in our investigation), and two drops rather than one were administered to each eye. In this study both bimatoprost and netarsudil showed significant decrease in IOP, however, bimatoprost was found to be more effective in decreasing IOP in all patients as compared to netarsudil especially more in higher base line group.…”
Section: Ss-oct For Rnfl Onh Gcccontrasting
confidence: 59%
“…Prostaglandin analogs improve uveoscleral outflow as an alternative way of the aqueous humor resorption. Containing prostaglandins, they amplify intraocular inflammation, so they should be avoided in XFG treatment ( 16 ). All of these agents contain benzalkonium chloride, a substance that provides prolonged shelf life of the opened vial of eye drops.…”
Section: Discussionmentioning
confidence: 99%
“…150 Recent studies have demonstrated that treatment with combined prostaglandin analogues and β-blockers more effectively suppressed the profibrotic genes expression in TM of patients with POAG compared to treatment with prostaglandin analogues alone or β-blockers alone. The study by Tejwani et al 151 observed that combination of bimatoprost and timolol lowered the TGFβ1 , TGFβ2 , CTGF , FN gene expression. It was also observed that CTGF expression was lower in β-blockers alone group compared to prostaglandin-alone group.…”
Section: Glaucomamentioning
confidence: 98%
“…The study also observed that the effects on profibrotic markers were modulated by inhibiting the phosphorylation of SMAD 3. 151…”
Section: Glaucomamentioning
confidence: 99%
See 1 more Smart Citation